Obdavčitev dela in zaposlenost v državah OECD in Sloveniji - Dolenc, Primož (Družboslovne razprave, 2011)
The paper assesses the characteristics of the tax wedge and employment in OECD countries and Slovenia and analyses the effect of the tax wedge on employment. OECD countries are characterised by a progressive tax wedge since it increases with one's earnings. In most countries the average tax wedge for families with two children is smaller than for single persons with the same earnings as they are entitled to cash benefits. The empirical estimates also show that, with regard to the employment and unemployment rates, OECD countries can be classified in two groups. The first group is characterised by a high tax wedge, low employment and high unemployment rates, whereas the second group has different characteristics. The negative effect of the tax wedge on employment was also confirmed in a panel regression analysis. Slovenia is ranked among those countries with a high tax wedge, and hence it is particularly important to continue with the dynamics of reducing the tax wedge.
Keywords: Delo; Labor; labour; Obdavčevanje; Taxation; Zaposlenost; Employment; Economic policy; Ekonomska politika; Slovenia; Slovenija; mednarodne organizacije; OECD